Challenges of Migrating Legacies Web to Mobile: A Systematic Literature Review - Cajas Cajas, Viviana Elizabeth (2020)
The multi-device era comes thanks to mobile computing which gives remote access to resources from anywhere changing the people’s life and opening new business opportunities. However, the legacy systems do not render the content properly in mobile devices because they were thought to be only compliant with Web browsers. Economic availability is often the reason why these have not been modernized. This work proposes a systematic literature review about the approaches used for the portabilization or modernization of web 1.0 business applications to mobile devices in the period 2006-2017, from SCOPUS, IEEE, and ACM. The search obtained 824 articles, 44 were selected and classified with respect to focus, scope, type of research and type of contribution. The results obtained allowed us to reach conclusions about the state of the subject and to determine the research gaps, such as the need for better use of the mobile characteristics because the adaptations are mostly basic. In addition, an approach is proposed and compared with the aforementioned them.